Quality assessment of measurement instrument software with analytic hierarchy process - Velychko, Oleh; Hrabovskyi, Oleh; Gordiyenko, Tetyana (Eastern-European Journal of Enterprise Technologies, 2019)
A comparative analysis of the results of conformity assessment of software for measuring instruments (MI) was carried out. For comparative evaluation, eight MI software with built-in and universal computers were selected. Selected MI software was preliminarily evaluated by methods and algorithms that are based on the requirements of national standards and documents of international and regional legal metrology organizations OIML and WELMEC. Based on the results of the analysis of the requirements of the WELMEC guidelines for testing MI software, generalized and particular indicators were selected for assessing the quality of MI software. Expressions to obtain the numerical value of each partial indicator for each generalized indicator was generated. For comparative evaluation, the analytic hierarchy process (AHP) was chosen, since it allows comparing and quantifying alternative solutions. For the purpose of relevant comparison, when evaluating a specific MI software, all compared elements were taken into account. The latter were grouped into generalized indicators, each of which was evaluated separately. Pairwise comparisons and all other stages of assessment using AHP were carried out on the basis of generalized indicators. For pairwise comparison of all quantitative and qualitative indicators with the presentation of the equation in a quantitative form, the Saati scale was used. The weight coefficients of each partial indicator were determined by the expert method. The main indicators for MI software with a built-in and universal computer were determined, which have the greatest impact on the results of conformity assessment. It was found that without the presentation of documentation and identification of MI software with built-in and universal computers, it is impossible to begin the conformity assessment procedure in accordance with the requirements. The test indicator of storage devices and the special test indicator of software for particular MI are some of the significant indicators. At the same time, the reading test indicator and the test indicator of software separation levels are practically not applicable and can be neglected.